Studi Kritis Atas ???Al-Tafs??r Al-Bay??ni Li Al-Qur?????n Al-Kar??m???Karya ?????isyah ???Abdurrahm??n Bintu Sy??ti??? (W. 1998 M.) - Aghnia Faradits (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Aisyah Abdurrahman or better known as Bintu Syati 'is a very famous female mufassirah in her era. The existence of Amin al-Khulli's style of thought - who is also Bintu Syathi's teacher and husband - made Aisyah Bintu Syathi's preference in explaining or using methods in her interpretation. The book that is in the hands of this author is Bintu Syati's monumental work in the field of interpretation "Al-Tafs??r Al-Bay??ni Li Al-Qur'??n Al-Kar??m" which is very concerned with enthusiasts of al-Qur'an studies. This book consists of two volumes, each of which includes 7 chapters, consisting of the letters al-Dhuha, al-Insyirah, al-Zalzalah, al-A'diyat, al-Nazi'at, al-Balad, and al-Takatsur. While the second volume consists of the letters al-Alaq, al-Qalam, al-Ashr, al-Lail, al-Fajr, al-Humazah and al-Ma'un. Thus this commentary only contains 14 short suras, taken from juz 'Ammah, chapter 30 of the Qur'an.After studying further, the style and method of interpretation of a person is greatly influenced by his intellectual background. Bintu Syati 'for example, as an interpreter with a literary background, of course, tries to look at the Qur'an from a literary perspective. By focusing on the method used by her husband, she was able to create several books of commentary-one of them is al-Tafsir al-Bayani li al-Qur'an al-Karim which consists of two volumes, each of which includes 7 short suras taken from juz 'Ammah, chapter 30 of the Qur'an.